SEDIMENT CONTAMINATION AND THE IMPLICATIONS OF ITS MINING IN THE ANAMBRA DRAINAGE BASIN, SOUTHEAST NIGERIA (Journal of Geography, Meteorology and Environment, 2021)
River sediments are mined in the Anambra drainage basin despite its contaminant loading. During the rainy and dry seasons, sediment samples were obtained from the six sub-basins at the upper and downstream segments and were subjected to geochemical and geotechnical analyses using X-ray fluorescence (XRF), X-ray diffraction (XRD) and scanning electron microscope (SEM) imaging. The soil samples collected were also analysed to determine its physical properties. It was noted that potential toxic elements (PTEs) - Zn, Ni, Mn, Fe, Cr, Pb, V, Mo, Sc and Eu, were within the World Health Organization recommended limits while contamination degree (CD), modified degree of contamination (mCd) and pollution load index (PLI) revealed that the sediment PTEs’ concentrations ranged between slight contaminations to severely polluted. Better sediment quality exists at the upstream during the rainy season. From, SEM, sediments showed high content of quartz. Particle size distribution (PSD), porosity –cum- bulk density, aggregate stability (AS), mean weight diameter (MWD), dispersion ratio (DR) and Roslan and Mazidah (ROM) scale of the soil suggests intense erosion as within the basin. Erosion and anthropogenic activities are major source of sediments and PTEs into the river channels.
Keywords: Anambra drainage basin; PTEs; Sediment mining; Erosion; Anthropogenic activities